Platinum porphyrin/3-(trimethoxysily)propylmethacrylate functionalized flexible PDMS micropillar arrays as optical oxygen sensors. (31st May 2017) - Mao, Yongyun; Zhao, Qian; Pan, Tingting; Shi, Jiayan; Jiang, Shimei; Chen, Meiwan; Zhou, Bingpu; Tian, Yanqing
Abstract : A PtTPP/TPMA functionalized PDMS-based micropillar array film was presented as a flexible optical oxygen sensor with efficiently improved sensing capabilities. Abstract : Integrating an oxygen-sensitive probe (OSP) onto a three-dimensional (3D) microstructure substrate is a plausible technique to significantly improve the sensitivity of oxygen sensors. Despite the fact that polydimethylsiloxane (PDMS) matrices are regarded as the ideal sensory support, there are still no reports on an OSP functionalized flexible PDMS-based micropillar array (PDMS-MPAs) film as an optical oxygen sensor with capabilities to efficiently improve the sensor's overall performance, e.g. sensitivity, detection limit and stability against photo-bleaching. Herein, we reported the covalent bonding of a functional copolymer of platinum porphyrin (PtTPP)/3-(trimethoxysily)propylmethacrylate (PtTPP/TPMA) as the OSP on the surface of hydroxyl-modified PDMS-MPAs through a "grafting reaction" between PtTPP/TPMA and PDMS-MPAs. The homogeneous dispersion and well-isolated arrangement of the PtTPP/TPMA OSP on the 3D PDMS-MPA surface can ensure that the grafted OSP efficiently quenches the oxygen molecules. Consequently, the 3D PtTPP/TPMA-PDMS-MPA sensor film gives rise to a high fluorescence quenching efficiency of about 95% at 1 atm O2 ( I 0 / I 100 = 23) and 96% in aqueous solution ( I 0 / I O2 satu = 16) with an excellent linear Stern–Volmer plot ( k sv = 0.1 h Pa −1, R 2 = 0.997 in gas atmosphere and k sv = 12.8 mmol −1 L, R 2 = 0.999 in aqueous solution, respectively), excellent reversibility and an ultra-low detection limit (4.7 μmol L −1 ) when compared with state-of-the-art PDMS-based oxygen sensors. Apart from the competitive sensitivity, the highly durable, reusable superiorities of the 3D PtTPP/TPMA-PDMS-MPA film can further facilitate the exploration and realization of the presented strategy for future oxygen sensor applications, such as the characterization of nearly anoxic systems in harsh environments.